Metallic Nano‐Composite Toxicity Evaluation by Zebrafish Embryo Toxicity Test with Identification of Specific Exposure Biomarkers. Issue 1 (13th February 2018) - Pecoraro, Roberta; Salvaggio, Antonio; Marino, Fabio; Caro, Gianfranco Di; Capparucci, Fabiano; Lombardo, Bianca Maria; Messina, Giuseppina; Scalisi, Elena Maria; Tummino, Maurizio; Loreto, Francesco; D'Amante, Giusi; Avola, Roberto; et al.
Abstract: Nanomaterials (NM) have different shapes and can be composed of different materials such as carbon, silicon, and some metals like gold, silver, and titanium. They are used as fillers, catalysts, semiconductors, cosmetics, drug carriers in medicine, energy storage systems, and antifriction coatings. NM are the parent compounds of nanoparticles (NPs), which may be divided into two groups: fullerenes and engineered nanoparticles (ENPs). After crossing the cell membrane, NPs may be stored in vesicles, mitochondria, and additional organelles within epithelial cells. They may generate reactive oxygen species, oxidative stress, and cytotoxicity, as well as denaturation of proteins, apoptosis, and necrosis. Nowadays, new toxicological data are required to assess the potential exposure of the environment and human beings to pollutants. The aim of the present investigation is to evaluate the toxicity of the metallic nano‐composite by the zebrafish embryo toxicity test (ZFET). The methods described here can be easily adapted to other nanocomposites or nanomaterials with some variations. © 2017 by John Wiley & Sons, Inc.